2019
DOI: 10.15666/aeer/1703_71897201
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Composition of Herby Cheese Produced From Raw and Pasteurized Milk

Abstract: In this study, the effects of sirmo (Allium vineale L.), mendi (Chaerophyllum macropodum Boiss.) and siyabo (Ferula rigidula DC.) on mineral compositions of herby cheese produced from raw and pasteurized milk in brine and vacuum package during 90 days ripening were determined. Macroelements (Ca, Mg, Na, K) and micro elements (Fe, Zn, Mn) concentration of herby cheese samples were examined by Inductively Coupled Plasma-Optical Emission Spectrometer (ICP-OES). It was determined that the mineral concentration was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 16 publications
(26 reference statements)
4
7
3
1
Order By: Relevance
“…Average K values of Orgu cheese samples in Table 3 were found to be higher than previous studies (Altun & Köse, 2016;Kose & Ocak, 2019;Ozlu et al, 2012). It is thought to be caused by dairy animals, geographical area of milk production, environmental conditions, possible contamination, and losses during the maturation period.…”
Section: Mineral Content Of Orgu Cheese Samplescontrasting
confidence: 63%
See 3 more Smart Citations
“…Average K values of Orgu cheese samples in Table 3 were found to be higher than previous studies (Altun & Köse, 2016;Kose & Ocak, 2019;Ozlu et al, 2012). It is thought to be caused by dairy animals, geographical area of milk production, environmental conditions, possible contamination, and losses during the maturation period.…”
Section: Mineral Content Of Orgu Cheese Samplescontrasting
confidence: 63%
“…It can be understood from Table 3 that the Mg values of Orgu cheese are significantly higher than the previous research results (Ozdemir et al, 1998;Çelebi, 2011;Ozlu et al, 2012;. In a study on Herby cheese (Kose & Ocak, 2019), it appears that the Mg concentration decreases during storage over time, similar to the Ca content. It was reported that 70% of the Mg was in soluble form and that Mg was transferred from the cheese to the brine during the storage period until the osmotic pressure between the brine and the cheese phase is equalized.…”
Section: Mineral Content Of Orgu Cheese Samplesmentioning
confidence: 61%
See 2 more Smart Citations
“…In recent years, studies on Herby cheese consisted mainly of the production technique of Herby cheese (Coşkun, 1995; 2005; Emirmustafaoğlu & Coşkun, 2012; Hayaloğlu & Fox, 2008; Tarakci & Temiz, 2009), the effect of different herbs on the composition of Herby cheese (Andic, Tuncturk, Javidipour, & Genccelep, 2015; Coşkun & Tunçtürk, 2000; Kavaz, Bakırcı, & Kaban, 2013; Tarakci, Durmaz, & Sagun, 2005; Tarakci & Kucukoner, 2006; Tarakci, Temiz, Aykut, & Turhan, 2011), comparison of Herby cheese produced by traditional and industrial methods (Kose & Ocak, 2019; Ocak, Javidipour, & Tuncturk, 2014; Tuncturk, Ocak, & Kose, 2014), and researches of Herby cheese samples obtained from the market (Andic et al., 2010; Ekici, Okut, İşleyici, Sancak, & Tuncay, 2019; Eralp, 1953; Hayaloglu & Karabulut, 2013; Isleyici, 1999; İsleyici & Akyuz, 2009; Koyuncu & Tuncturk, 2020; Kurt, 1968; Kurt & Akyüz, 1984; Ocak & Köse, 2010; 2018; Ozcan, Yılmaz‐Ersan, Akpinar‐Bayizit, & Delikanli‐Kiyak, 2017; Ozrenk, Kose, & Ekin, 2009; Sancak, 1989; Sancak, Boynukara, & Yardımcı, 1993; Sönmezsoy, 1994; Tuncay & Sancak, 2018). Researches on Herby cheese samples obtained from the market were also evaluated with some routine and physical, chemical properties, and microbiological aspects of Herby cheese samples.…”
Section: Introductionmentioning
confidence: 99%